2013
DOI: 10.1021/pr3010937
|View full text |Cite
|
Sign up to set email alerts
|

Application of Label-Free Shotgun nUPLC–MSE and 2-DE Approaches in the Study of Botrytis cinerea Mycelium

Abstract: The phytopathogenic fungus Botrytis cinerea infects more than different 200 plant species and causes substantial losses in numerous crops. The B05.10 and T4 wild-type strain genomes have been recently sequenced, becoming a model system for necrotrophic pathogens, as well as opening up new alternatives in functional genomics, such as proteomics. We analyzed B. cinerea mycelium from these two wild-type strains, introducing label-free shotgun nUPLC-MS(E) methodology to complement the 2-DE-MS-based approach. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 43 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…However, the complementarity of gel-based and gel-free proteomics approaches was suggested previously (Luque-Garcia et al, 2011; Abdallah et al, 2012). The combination of gel-based and gel-free proteomics was shown to be effective for the analyses of soybean under flooding (Yin et al, 2014), phytopathogenic fungus Botrytis cinerea (Gonzalez-Fernandez et al, 2013), Nicotiana tabacum trichomes (Van Cutsem et al, 2011), the honeybee hemolymph proteome (Bogaerts et al, 2009), or during soybean seed filling (Agrawal et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…However, the complementarity of gel-based and gel-free proteomics approaches was suggested previously (Luque-Garcia et al, 2011; Abdallah et al, 2012). The combination of gel-based and gel-free proteomics was shown to be effective for the analyses of soybean under flooding (Yin et al, 2014), phytopathogenic fungus Botrytis cinerea (Gonzalez-Fernandez et al, 2013), Nicotiana tabacum trichomes (Van Cutsem et al, 2011), the honeybee hemolymph proteome (Bogaerts et al, 2009), or during soybean seed filling (Agrawal et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Membrane protein preparations were obtained according to the method described by Molloy et al [23] with minor variations [24]. Subsequent analysis of these proteins was performed by the Proteomics Core Facility-SGIKER at the University of the Basque Country, using the protocol previously described by Gonzalez-Fernandez et al [25]. Briefly, after protein precipitation by using a 2D Clean-Up Kit (GE Healthcare), the pellet was suspended in RapiGest solution (0.2%) (Waters Corporation) and heated at 85°C for 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides were eluted with a linear gradient of acetonitrile (120 min from 3 to 40% and 15 min from 40 to 60% [v/v]). Mass spectra were acquired using a data-independent acquisition mode (MSE) [26] as previously described by Gonzalez-Fernandez et al [25] and processed with ProteinLynx Global SERVER v2.4 Build RC7 (Waters Corporation). Protein identification was carried out using the database search algorithm of the program [27] and the parameters specified by Parada et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have analyzed Xanthomonas protein accumulation in the presence of plant extracts and even fewer under in vivo conditions . Recently, high throughput proteomic techniques have been increasingly used to study plant pathogens and have revealed a better view of the changes that occur in protein accumulation . We have previously analyzed the proteome of Xcc during the interaction with Brassica oleracea , using an in vivo system and 2DE, however a low number of proteins could be detected and identified .…”
Section: Introductionmentioning
confidence: 99%